Cook–Swartz Doppler Probe Surveillance for Free Flaps—Defining Pros and Cons - Paprottka, Felix J.; Klimas, Dalius; Krezdorn, Nicco; Schlarb, Dominik; Trevatt, Alexander E. J.; Hebebrand, Detlev (The Surgery Journal, 2020)
Introduction The main postoperative complication of free flaps is perfusion compromise. Urgent intervention is critical to increase the chances of flap survival. Invasive flap perfusion monitoring with direct blood flow feedback through the Cook–Swartz Doppler probe could enable earlier detection of perfusion complications.Materials and Methods Between 2012 and 2016, 35 patients underwent breast reconstruction or defect coverage after trauma with a deep inferior epigastric perforator, anterolateral thigh, transverse musculocutaneous gracilis, gracilis, or latissimus dorsi flap in our department. All flaps were monitored with a Cook–Swartz probe for 10 days postoperatively. The 20 MHz probe was placed around the arterial–venous anastomosis. A flap monitoring protocol was established for standardized surveillance of postoperative perfusion. In the event of probe signal loss, immediate surgical revision was initiated.Results Signal loss was detected in 8 of the 35 cases. On return to the operating room, six were found to be true positives (relevant disruption of flap perfusion) and two were false positives (due to Doppler probe displacement). There were also two false negatives, resulting in a slowly progressive partial flap loss. Flap perfusion was restored in three of the six cases (50%) identified by the probe. Following surgical intervention, three of the six cases had persistent problems with perfusion, resulting in two total flap losses and one partial flap necrosis leading to an overall 5.7% total flap loss.Conclusion Postoperative flap perfusion surveillance is a complex matter. Surgical experience is often helpful but not always reliable. The costs, false-positive, and false-negative rates associated with invasive perfusion monitoring with Cook–Swartz probe make it most appropriate for buried flaps.Level of Evidence This is an original work.
Keywords: flap surveillance; flap survival rate; perfusion monitoring; DIEP flap; ALT flap; TMG flap